Critical Perspectives on Successful Aging: Does It "Appeal More Than It Illuminates"?. (18th April 2014) - Katz, Stephen; Calasanti, Toni
Abstract : "Successful aging" is one of gerontology's most successful ideas. Applied as a model, a concept, an approach, an experience, and an outcome, it has inspired researchers to create affiliated terms such as "healthy, " "positive, " "active, " "productive, " and "effective" aging. Although embraced as an optimistic approach to measuring life satisfaction and as a challenge to ageist traditions based on decline, successful aging as defined by John Rowe and Robert Kahn has also invited considerable critical responses. This article takes a critical gerontological perspective to explore such responses to the Rowe–Kahn successful aging paradigm by summarizing its empirical and methodological limitations, theoretical assumptions around ideas of individual choice and lifestyle, and inattention to intersecting issues of social inequality, health disparities, and age relations. The latter point is elaborated with an examination of income, gender, racial, ethnic, and age differences in the United States. Conclusions raise questions of social exclusion and the future of successful aging research.